Pengaruh Self-Assessment, Kesadaran Wajib Pajak, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Pribadi - Urfatul Rustaprilana; Agustina, Heni; Khusnah, Hidayatul (Universitas Nahdlatul Ulama Surabaya, 2022)
This study aims to examine the effect of self-assessment, taxpayer awareness, and tax sanctions on taxpayer compliance. The data used in this study using primary data. Primary data obtained through questionnaires distributed to taxpayers in the West Sidoarjo region. This study uses a data collection technique which uses the slovin formula with a sample of 100 taxpayers having a TIN. The type in this research is quantitative. The population in this study is an individual taxpayer in West Sidoarjo. The analysis used is multiple linear analysis and uses the SPSS 25 program. The results of the study indicate that the self-assessment variable, taxpayer awareness, and tax sanctions have a significant effect on taxpayer compliance in paying personal taxes. However, partially the self-assessment variable has a significant positive effect on taxpayer compliance. Meanwhile, the taxpayer awareness variable has no significant effect on taxpayer compliance. And the variable of tax sanctions has a significant positive effect on taxpayer compliance.